Review: Implementation of Overall Equipment Effectiveness (OEE) Based on Lean Manufacturing Tools in the Indonesian Pharmaceutical Industry - Prilly Mutiara Sandy; Nasrul Wathoni (Universitas Padjadjaran (Unpad), 2022)
Increasing production in the industry is important to face the current global competition. Therefore, a performance measurement system is needed for the manufacturing process. Overall Equipment Effectiveness (OEE) is a method for monitoring and improving the efficiency of manufacturing processes. In this article, overall equipment effectiveness (OEE) is described as one of the performance measurement tools that measure different types of production losses and shows areas of process improvement. The analysis is done on how OEE evolved leads to other tools such as the performance of the total equipment effectiveness, such as the effectiveness of production equipment, the effectiveness of the overall plant, and the effectiveness of the asset as a whole. OEE consist of three metric measurement; availability, performance, and quality. Purpose of review articles is to apply these metrics to compare the efficiency and effectiveness of production activity in pharmaceutical industry and to categorize the highly occurence of loss productivity in the production activity that takes place in industry, especially pharmaceutical industry. This review included studies published in ScienceDirect database with the keyword “Lean Manufacturing” and “Overall Equipment Effectiveness”. The results obtained from study of the primary source is the OEE can be used to optimize the production process in the industry, especially the pharmaceutical industry, because this method can produce products efficiently and with the good quality of products that leads to consumer’s satisfactory.